Cutaneous metastasis from esophageal basaloid squamous cell carcinoma: A case report. (March 2021) - Endo, Fumitaka; Akiyama, Yuji; Onishi, Masazumi; Uesugi, Noriyuki; Sugai, Tamotsu; Sasaki, Akira
Highlights: Cutaneous metastasis of esophageal cancer is rare. Basaloid squamous cell carcinoma (BSCC) of the esophagus is a relatively rare histologic variant of squamous cell carcinoma. We reported a case of cutaneous metastasis from esophageal BSCC and was successfully treated with multidisciplinary treatment. Abstract: Introduction and importance: Basaloid squamous cell carcinoma (BSCC) of the esophagus is a relatively rare histologic variant of squamous cell carcinoma. Here, we reported a case of solitary cutaneous metastasis as the first symptom of esophageal BSCC and was successfully treated with multidisciplinary treatment. Case presentation: A 67-year-old man visited a local hospital with symptoms of dysphagia and cutaneous nodules on his left shoulder. Fluorine-18 fluorodeoxyglucose positron emission tomography revealed hypermetabolic accumulations in the middle thoracic esophagus, right recurrent laryngeal nerve lymph node, and epidermis of the left shoulder. Esophagogastroscopy revealed an ulcerative and infiltrating type tumor in the middle thoracic esophagus. Based on histopathologic examination of the endoscopic biopsy and the resected cutaneous tumor, the patient was diagnosed as esophageal BSCC with cutaneous metastasis. The patient was treated with chemotherapy followed by chemoradiotherapy. The therapeutic effect was a complete response, which was sustained for 39 months. Clinical discussion: Review of previous literature in the PubMed database revealed only been two case reports on cutaneous metastasis of BSCC. Advanced BSCC of the esophagus with distant metastasis has a poor prognosis. Therefore, in our case, future careful follow-up is required. Conclusion: Esophageal BSCC with cutaneous metastasis can be successfully managed by multidisciplinary treatment, including local resection of the cutaneous metastasis, systemic chemotherapy, and chemoradiotherapy.